Fundação de Serralves : Um Museu Portugues. - Pernes, Fernando; Pinharanda, Joao; Pinto de Almeida, Bernardo; Fundação de Serralves, Porto; Universal Expo '92, Sevilla (Sevilla, Comissariado de Portugal para a Exposição Universal de Sevilha, 1992)
Carneiro, Alberto ; de Sousa, Angelo ; Pinto, Antonio Cerveira ; Dacosta, Antonio ; Iglesias, Cristina ; Riverhead (New York) ; Oppenheim, Dennis ; Judd, Donald ; Burmester, Gerardo ; Merz, Gerhard ; Zorio, Gilberto ; Steinbach, Haim ; Croft, José Pedro ; Muñoz, Juan ; Moura, Leonel ; Rosa, Manuel ; Muntadas, Antoni ; Cabrita Reis, Pedro ; Proença, Pedro ; Gober, Robert ; Sanches, Rui ; Cragg, Tony (Anthony) ; Laib, Wolfgang
biografie
Expo '92 Sevilla, June 26 to July 15 1992
Engels & Portugees
boek